Micellisation behavior on the dodecyltrimethylammonium bromide in the presence of Brij-35 in pure water by conductivity measurement - Shahi, Neelam; Bhattarai, Ajaya (BIBECHANA, 2017)
Conductivity measurement of dodecyltrimethylammonium bromide in the presence of Brij-35 in aqueous media at 289.15 K is performed. The result showed a sharp increase in conductivity with increase in the concentration of dodecyltrimethylammonium bromide in the presence of Brij-35. The graph of specific conductivity versus concentration is used in determining the critical micelle concentration (CMC). There is the decrease in CMC of dodecyltrimethylammonium bromide in the presence of Brij-35 in comparison with the CMC of dodecyltrimethyl ammonium bromide [DTAB]. Gibbs free energy of micellisation has also been evaluated. BIBECHANA 15 (2018) 85-89